Collision-induced stimulated photon echoes in 'strong' magnetic field. (3rd April 2018) - Reshetov, V A
Abstract: Collision-induced stimulated photon echoes formed in a gaseous medium on the transition with the angular momentum change J a = 0 → J b = 1 under the action of 'strong' longitudinal magnetic field, when the echo pulse becomes unpolarized, are considered with an account of elastic depolarizing collisions. In the case of narrow spectral line the explicit expressions for the echo polarization density matrix and the degree of polarization are obtained. In the case of broad spectral line the results of the numeric calculations reproduce qualitatively the curve obtained in the experiments with ytterbium vapor.